CHANGING SOCIETY’S VIEW OF PRISON: A HUMAN RIGHTS INTERVENTION (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2026)
The prison system is examined from a critical and decolonial perspective, highlighting its structural incompatibility with human rights. It is argued that incarceration, rather than promoting justice or rehabilitation, reproduces social, racial, and economic inequalities, operating as a mechanism of control and exclusion of marginalized populations. The dominant punitive logic, the normalization of institutional violence, and the silencing of human rights violations within prisons are critically addressed, with particular attention to racialized groups, the poor, Indigenous peoples, women, and children. The need to transform penal language, practices, and policies is emphasized, prioritizing restorative justice, social reintegration, and the confrontation of structural causes of crime, such as poverty, inequality, and social exclusion. It is concluded that placing human rights at the center is essential for developing alternatives to mass incarceration.